Application of Differential Evolution Algorithm in the Construction and Simulation of Interactive English Translation Teaching Mode - Chi Che (Advances in Multimedia)
To improve the effect of English translation teaching, this paper combines the differential evolution algorithm to construct and simulate the interactive English translation teaching mode and analyzes the differential enumeration attack. Moreover, this paper studies the algorithm structure of the LowMC algorithm and evaluates the rationality of the LowMC algorithm round number setting by analyzing the actual attack effect of the key initial round number of a specific linear layer. Additionally, by studying whether the key initial round number can reach the theoretical value under the actual linear layer, the effect of differential evolution algorithm processing teaching information is evaluated. Through expert evaluation, it can be seen that the interactive English translation teaching model based on the differential evolution algorithm proposed in this paper has good effects and can improve the quality of English translation teaching.